Mulberry twig alkaloids for type 2 diabetes mellitus: a systematic review and meta-analysis - Guoming Chen; Ruifeng Yang; Xiaoya Yang; Jiazhen Jiang; Yudan Guo; Mengshan Xu; Yi Chen; Yining Hou; Cheng Zhang; Ning Wang; Yibin Feng (Frontiers in Pharmacology)
BackgroundDiabetes has emerged as a significant global health concern, with over 95% of cases categorized as type 2 diabetes mellitus (T2DM). The disease not only imparts detrimental effects on individual health but also imposes a substantial burden on societal economics and healthcare systems. Notably, there is a paucity of meta-analyses on the efficacy of mulberry twig alkaloids (MTAs) for the treatment of T2DM.MethodsThe systematic review registration number is CRD42024523218. Data were retrieved from Cochrane Library, ClinicalTrials.gov, Embase, PubMed, Ovid, Web of Science, China National Knowledge Infrastructure (CNKI), Scopus, Chongqing VIP, CINAHL, SINOMED, ChiCTR, and Wanfang Data from their inception to 1 February 2024 for herbal product-related randomized controlled trials (RCTs). The risk of bias assessment and meta-analysis were performed using ReviewManager 5.4 and STATA 15.0. TSA software version 0.9.5.10 was used to assess whether the results achieved the required information size (RIS). GRADEprofiler 3.6 software was used to estimate the quality of evidence for the outcomes.ResultsNine studies were included for a total of 10 trials with 1,178 patients. The results indicated that MTAs were more effective than placebo in reducing HbA1cglycated hemoglobin (HbA1c), and MTAs combined with hypoglycemic drugs were more effective than hypoglycemic drugs alone in reducing HbA1c, fasting blood glucose (FBG), and 2-hour postprandial glucose (2hPG). In terms of lipid control, MTAs combined with hypoglycemic drugs showed better control of triglycerides (TGs) and low-density lipoprotein (LDL) efficacy than hypoglycemic drugs alone. After MTA treatment, there was no damage to liver function compared to placebo. The safety of MTAs, whether alone or in combination with hypoglycemic drugs, was comparable to that of hypoglycemic drugs alone.ConclusionIn T2DM patients, MTAs were more effective than placebo. MTAs combined with hypoglycemic drugs showed better results than hypoglycemic drugs alone. The safety of MTAs was equivalent to that of hypoglycemic drugs. However, due to heterogeneity and possible bias, the results should still be interpreted with caution.Systematic Review Registrationhttps://www.crd.york.ac.uk/PROSPERO/display_record.php?RecordID=523218